Risco, direito e decisão: reflexões acerca do uso de células-tronco em pesquisas no Brasil: uma abordagem a partir de Beck, Giddens e Luhmann - Ferreira, Fernanda Busanello (My University, 2014)
The contemporanity points with respect to a new conception of the risk. One transfers of an idea of control and rationality for an uncertainty idea and probabilities. These transformations reflect in the system of the right that is obliged to decide and to face the problems of the current society. The form as the matrices of the right has dealt with the risk is object of this research. Ahead of this context, the case of the advance of the technology, more necessarily is presented, the controversial use of the stem cells as a question that the right must answer. Reflections on the uncertainty and the contingency of the use of these technologies will be made in order to verify the sistemic use of the right as way to observe the involved complexity in the question, using for this the theory by Beck, Giddens and Luhmann.
A contemporaneidade aponta para uma nova concepção do risco. Passa-se de uma idéia de controle e racionalidade para uma idéia de incerteza e probabilidades. Essas transformações refletem no sistema do direito, que é obrigado a decidir e enfrentar os problemas da sociedade atual. A forma como as matrizes do direito têm lidado com o risco são objeto desta pesquisa. Diante desse contexto, apresenta-se o caso do avanço da tecnologia, mais precisamente o uso polêmico das células-tronco como uma questão que o direito deve responder. Reflexões sobre a incerteza e a contingência do uso dessas tecnologias serão feitas a fim de verificar o uso sistêmico do direito como modo de observar a complexidade envolvida na questão, utilizando-se, para isso do substrato oferecido pela teoria de Beck, Giddens e Luhmann.
Keywords: Direito; Racionalidade; Tecnologia; Células-tronco; Rationality; Technology; Stem cells; Beck, Ulrich, 1944-; Giddens, Anthony, 1938-; Luhmann, Niklas; Direito; Racionalidade; Tecnologia; Células-tronco; Beck, Ulrich, 1944-; Giddens, Anthony, 1938-; Luhmann, Niklas; Rationality; Technology; Stem cells